Primary care physicians and pandemic influenza: An appraisal of the 1918 experience and an assessment of contemporary planning - Lauer, Jacob; Kastner, Justin; Nutsch, Abbey L. (My University, 2009)
This multidisciplinary research project examined the role of primary care physicians in past pandemic flu responses and current planning efforts. Project researchers gathered and synthesized historical research, state and federal planning documents, and interview-based data. The 1918 influenza pandemic presented one model from which to understand the role played by physicians during a large-scale disease outbreak, and the challenges they faced. Contemporary planning documents were assessed for their inclusion of primary care physicians. Literature reviews and interviews comprised the principal sources of information. Findings included the following: (1) primary care physicians do not have the time to engage fully in pandemic planning activities; (2) physicians are willing to serve during a pandemic; however, government support and the availability of resources will affect their level of involvement; (3) communities should develop plans for coordinating local physicians that will allow alternative care sites to be functionally staffed; and (4) full coordination of physicians is not possible under the U.S. healthcare system.
Keywords: Primary care physicians; Pandemic influenza 1918; Assessment of contemporary planning; Healthcare; Pandemic; Flu